PHYSICO^CHEMICAL PROPERTIES OF VEGETABLE AND FRUIT PRODUCTS AND ESPECIALLY ITS STORAGE IN A COLD STATE - S. V. Murashev; N. N. Sharagova (Kalatsevich) (Овощи России)
The influence of the state of water in plant tissue on the physico- chemical properties of plant products and processes occurring in it was studied. It is shown that the ratio of free and bound water fractions in the tissue influences the mass loss of plant products during storage. The ratio between free and bound water in the plant tissue depends on the activity of physiological processes in it, which determines the intensity of the loss of nutrients.